Obelia geniculata - Gil, Marta; Ramil, Fran (Zenodo, 2021)
Obelia geniculata (Linnaeus, 1758) Sertularia geniculata Linnaeus, 1758: 812. Laomedea geniculata – Broch 1914: 37. Obelia geniculata – Millard 1975: 229–230, fig. 75a–b. — Cornelius 1995: 301–303, fig. 70. — Calder 2012: 50–51, fig. 53. Material examined SOUTH ATLANTIC OCEAN •3 colonies, up to 5 mm high (all growing on brown algae, 2 colonies, with gonothecae); Vema Seamount, stn BT5; 31°37′16″– 31°36′58″ S, 8°22′37″– 8°23′06″ E; 71–94 m depth; 31 Jan. 2015; SEAFO-2015 leg.; SEAFO-2015-40317, SEAFO-2015-40327, SEAFO-2015-40768. Distribution Usually considered as a cosmopolitan species, with records from all oceans (Peña Cantero & García Carrascosa 2002), although absent from Antarctic waters (Peña Cantero 2004). In the Southeast Atlantic, it was recorded from Namibia (Broch 1914, as Laomedea geniculata (Linnaeus, 1758)), Vema Seamount (Millard 1966) and South Africa (Millard 1975). Its bathymetric distribution extends from the intertidal (Cornelius 1995) to 381 m (Gili et al. 1989). : Published as part of Gil, Marta & Ramil, Fran, 2021, Hydroids (Cnidaria, Hydrozoa) from the Vema and Valdivia seamounts (SE Atlantic), pp. 49-96 in European Journal of Taxonomy 758 on page 66, DOI: 10.5852/ejt.2021.758.1425, http://zenodo.org/record/5088125 : {"references": ["Linnaeus C. 1758. Systema naturae per regna tria naturae, secundum classes, ordines, genera, species cum characteribus, differentiis, synonymis, locis. Editio decima, reformata. L. Salvius, Stockholm. https: // doi. org / 10.5962 / bhl. title. 542", "Broch H. 1914. Hydrozoa benthonica. In: Michaelsen W. (ed.) Beitrage zur Kenntnis der Meeresfauna Westafrikas. Volume 1: 19 - 50. L. Friederichsen & Co., Hamburg.", "Cornelius P. F. S. 1995. North-West European Thecate Hydroids and their Medusae. Part 2. Sertulariidae to Campanulariidae. In: Barnes R. S. K. & Crothers J. H. (eds) Synopses of the British Fauna (New Series) 50. Field Studies Council, London.", "Calder D. R. 2012. On a collection of hydroids (Cnidaria, Hydrozoa, Hydroidolina) from the west coast of Sweden, with a checklist of species from the region. Zootaxa 3171 (1): 1 - 77. https: // doi. org / 10.11646 / zootaxa. 3171.1.1", "Pena Cantero A. L. & Garcia Carrascosa A. M. 2002. The benthic hydroid fauna of the Chafarinas Islands (Alboran Sea, western Mediterranean). Zoologische Verhandelingen, Leiden 337: 1 - 180.", "Millard N. A. H. 1966. Hydroids of the Vema Seamount. Annals of the South African Museum 48: 489 - 496.", "Gili J. M., Vervoort W. & Pages F. 1989. Hydroids from the West African coast: Guinea Bissau, Namibia and South Africa. Scientia Marina 53 (1): 67 - 112."]}